Harvest systems and residue management of sugarcane - Souza, Zigomar Menezes de; Prado, Renato de Mello; Paixão, Antônio Claret Strini; Cesarin, Luiz Gilberto (Pesquisa Agropecuaria Brasileira, 2005)
The use of sugarcane harvesting without residue burning is a common harvesting management in Brazil. The objective of this work was to evaluate the effect of harvest systems and management of sugarcane with and without trash incorporation and of burned sugarcane on soil physical attributes as on production of stems in a Red Yellow Latosol (Typic Hapludox). The treatments can be described as sugarcane (Saccharum officinarum) with burning and manual cutting; sugarcane without burning and automated cutting, with incorporation of chopped residue down to 0.30 m; sugarcane without burning and automated cutting, without incorporation of chopped residue. The particle size distribution, soil organic matter, aggregate stability, bulk density and soil porosity in 0.0–0.1, 0.1–0.2 and 0.2–0.3 m depths were determined as well as soil resistance to penetration and soil moisture in 0.0–0.1, 0.1–0.2, 0.2–0.3 and 0.3–0.4 m depths. The systems sugarcane without burning and sugarcane with residue incorporation revealed the highest stalk production and higher values of organic matter, aggregate stability, macroporosity, water content and smaller values of soil resistance to penetration and bulk density of soil, compared to sugarcane system without incorporation of residue and burned sugarcane.